Male academic underachievement in Trinidad and Tobago:: Nature, antecedents, & consequences: A review and analysis - De Lisle, Jerome (My University, 1997)
This paper is concerned with chronic, broad underachievement among male students in the school system of Trinidad and Tobago. The standard used to assess male underachievement in the school system was based on the expected performance of the male sub-population on aptitude tests, as a component of the general population. In order to ensure that valid and reliable generalizations were made about the differences in achievement between males and females, the study based its conclusions on analyses of a breadth of statistical data, which covered key educational indicators such as subject enrolment, school enrolment, dropout and grade repetition rates, as well as an assessment of pass rates. Unfortunately mean scores by gender were not readily available in most of the key local high stakes examinations (except 14+), so that alternative methods of assessing achievement were derived, for example, in the case of the Caribbean Examinations Council (CXC) examinations, the number of males and females obtaining Grades I and II were used as a measure of overall achievement. The study concludes that male underachievement is a growing problem in Trinidad and Tobago, and suggests that intervention strategies must be targeted in terms of: 1) institutional policies and processes ; 2) classroom interaction processes; 3) the development of school based, gender-relevant programmes for boys ; 4) the provision of attribution and motivation training for all students; 5) teacher sensitization; and 6) parent involvement programmes targeting fathers and boys.
Keywords: Male underachievement